Perancangan Prototype Web Profile Desa Wisata Dan Kerajinan Gamplong Sleman Dengan Metode Desain User Experience - Dian Prajarini (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2018)
Gamplong Tourism Village and Craft at Sleman Regency are one of the alternative tourist destinations of Yogyakarta Special Region. This tourist village presents weaving craft tours. There are approximately 18 weaving craftsmen in this tourist village. The promotions that have been carried out so far are still using leaflet and social media usage methods. It is an obstacle when social media does not provide clear information for tour packages in Gamplong tourism and craft villages. The absence of a website as a showroom and provider of information about the details of Gamplong tourism villages and handicrafts. This research develops a Gamplong village tourism and craft web profile prototype uses user experience design method. The design method uses five planes user experience elements. The design result evaluation method uses a heuristic evaluation method. The results of the study succeeded in creating a prototype web profile of Gamplong Tourism Village and Craft with user experience design method. The heuristic evaluation results on the interface of the Gamplong Tourism Village's prototype web profile and Handicraft as a reference for usability evaluation, suggesting that aesthetics, design, and match with the real, but need better handling for error prevention, adding help menus, and bilingual features.